New Perspectives on Prison Masculinities (Palgrave Studies in Prisons and Penology, 2018)
This edited collection utilises recent advances in theories on masculinities to explore and analyse the ways in which prisons shape performances of gender, both within prison settings and following release from prison. The authors assess here how the highly gendered world of the prison (where the population is overwhelmingly male in most countries) impacts upon the performance of masculinities. Including original pieces from England, Australia, Scotland and the USA, as well as contributions which take a broader methodological and conceptual approach to masculinity, this engaging and original collection holds international appeal and relevance. Cumulatively, the chapters illustrate the importance of considering a nuanced understanding of masculinity within prison research, and as such, will be of particular interest for scholars of penology, gender studies, and the criminal justice system.